KEANEKARAGAMAN TIPE TUTURAN KRAMA PADA MASYARAKAT JAWA PESISIR SEBAGAI BENTUK KEDINAMIKAAN DAN KETERBUKAAN BAHASA JAWA KEKINIAN - Suryadi, Muhammad (HUMANIKA, 2018)
ABSTRACTThe Javanese language that developed in the Coastal Region could change (development) in a shape and type of speaking. The Javanese language that developed in the Coastal Region could have change (development) in a form and type of speaking. The changes on a shape was dominated by a variant of lexicon (dialectic). The changes on speaking type tended to occur in the understanding and speaking krama. This research was focused on changing the type of speaking krama language.The Location of research in Semarang city as a part of the coastal region. Data collection used the observation methods, in-depth interview, structured interview and focus group discussion. Data analysis used a sorting elements method of lingual targets, and column method that based on column and row.The findings of research was the emergence of variety of the type on speaking krama on the coastal Java community in Semarang City as a dynamic form and openness at Recency of Javanese Language.The direction of diversity sequence was still rooted in the core of Javanese Language standards.The four type discovered on krama, namely standard of krama, kramanisasi themselves, naturalization and migration lexicon.